'We Didn't Kill Any Babies': The 1988 Rebel Track and Field Tour of South Africa. Issue 8 (15th July 2022) - Sikes, Michelle M.; Fredericks, Jacob J.; Rodríguez, Paulina A.; Macedo, Emmanuel; Poorman, Michael; Lyons, Matthew; Pandit, Rucha; Dyreson, Mark
ABSTRACT: Just after the 1988 Seoul Olympics concluded, a handful of US athletes defied national and international customs and codes and accepted invitations to compete in South Africa, then a pariah state barred from international athletic competitions by almost every global sporting organization. The sporting boycotts represented one phalanx of the decades-long campaign to isolate South Africa until it dismantled apartheid. The US team included both white and Black athletes, as well as women and men. Condemned by many of their fellow athletes, international sporting officials, and the world press corps as mercenaries bent on violating the embargo righteously imposed on apartheid South Africa for a lucrative payday, the 'rebel' track and field team fought back. They declared that their interracial goodwill visit would do more to undermine apartheid than boycotts, proclaimed themselves as missionaries determined to change the world, and condemned their critics as hypocrites who denied athletes the rights of free expression and choice while encouraging sporting interchanges with other 'pariah nations', including Iran, North Korea, the Soviet Union, and the People's Republic of China. The tour became an international sensation that highlighted tensions over how to best fight apartheid while also changing the careers of many of the athletes involved.